Expressão do gene xynB5 que codifica uma -Xilosidase multifuncional de Caulobacter crescentus - Justo, Priscila Innocenti (2014)
The genetic manipulation of microorganisms has provided great advances in the production of enzymes involved in the bioconversion of biomass to fuels and chemicals. The main component of hemicellulose that compose the plant biomass is xylan, and its degradation dependent on the synergistic action of several enzymes, including xylanases and β-xylosidases stand as the major. The analysis of the genome of Caulobacter crescentus showed that this bacterium has at least eight genes encoding enzymes involved in the degradation of xylan, three coding for endo-xylanases and five β-xylosidases. In the present report, the enzymatic characterization of a C. crescentus β-glucosidase/β-xylosidase V was performed. For this purpose the xynB5 gene (CCNA 03149) was cloned into pJET1.2 /blunt and subcloned into the expression vector pTricHisA for producing a recombinant protein fused to an amino-terminal His-tag. The recombinant enzyme was induced with IPTG in E. coli (TOP10 strain) and the protein was purified using pre-packaged nickel-sepharose column. The characterization of the pure enzyme showed an optimum pH of 6 for both enzyme activity and a temperature optimum of 50 ° C to β-glucosidase and 60 ° C to β-xylosidase in the presence of NPG and NPX substrates, respectively, while also there has been a small activity in the presence of NPA. The multifunctional protein had its predominant enzyme activity to β-glucosidase (7.6 U ml-1) and a secundary β-xylosidase activity (4.3 U ml-1). In addition to greater specificity for NPG (Km = 0.24  0.008 mM) compared to that obtained for NPX (Km = 0.64  0.032 mM) although the Vmáx for both substrates was not statistically significant difference in optimal conditions of each enzyme (NPG = 0.041  0.001 M min-1 and NPX = 0.055  0.002 M min-1). In fact, data to enzymatic characterization corroborated the suggested in genomic annotation to C. crescentus. These multifunctional characteristics of the protein are important for biotechnological applications like the future reuse of agroindustrial residues